Designing a management approach for successful adoption of scrum - Buquiz, Joenille P.; Orendain, Nicole (Quezon City University of the Philippines Diliman, 2014)
A management approach for successful adoption of Scrum by software development companies in the Philippines is presented in this study. The management approach is designed based on identified gaps in five Scrum teams. The design likewise drew from concepts and best practices of Scrum and organizational change management. Further, the identified gaps in the five teams are addressed by the proposed approach. There is an increasing trend in the adoption of Agile methodologies by software development companies. (VersionOne, 2013) Agile is a conceptual framework of iterative and incremental development that advocates collaboration, adaptability, unity, simplicity and transparency. Among several Agile methodologies, the most popular is Scrum. It is estimated that a majority of teams who use Scrum are not reaping the benefits of the methodology. (Ken Schwaber on ScrumBut, 2010) Organizational culture and resistance to change are the usual barriers to successful adoption of Scrum. On the other hand, the most important success factor when adopting Scrum is executive sponsorship. Other strategies include training, coaching, effective communication, collaborative work, knowledge sharing, and continuous improvement. Five Scrum teams from three software development companies in the Philippines participated in the survey. The organizational change management approaches used by the companies were appraised based on the ADKAR model. The teams' compliance with Scrum was likewise assessed. A Scrum checklist was used for this purpose. The concepts in organizational change management were analyzed. Several tactics and techniques were recommended for each component of the ADKAR model. Teams adopting Scrum are advised to gain proficiency in the methodology by fully complying with Scrum. Prematurely changing and experimenting on the process will lead to failure in obtaining the benefits of Scrum.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Scrum (Computer software development) .; Management